Isolation, Potential Virulence, and Population Diversity of Listeria monocytogenes From Meat and Meat Products in China - Chen, Moutong; Cheng, Jianheng; Zhang, Jumei; Chen, Yuetao; Zeng, Haiyan; Xue, Liang; Lei, Tao; Pang, Rui; Wu, Shi; Wu, Haoming; Zhang, Shuhong; Wei, Xianhu; et al. (Frontiers in Microbiology, 2019)
Listeria monocytogenes is a globally notoriousfoodborne pathogen. This study aimed to qualitatively and quantitatively detect L. monocytogenes from meat and meat products in China and to establish their virulence profiles and population diversity. From 1212 meat and meat product samples, 362 (29.9%) were positive for L. monocytogenes. Serogroup analysis showed that the most prevalent serogroup of L. monocytogenes was I.1 (1/2a-3a), which accounted for 45.0% (123/458) of the total, followed by serogroup I.2 (1/2c-3c) that comprised 26.9%, serogroup II.1 (4b-4d-4e) that comprised 4.8%, and serogroup II.2 (1/2b-3b-7) that comprised 23.3%. A total of 458 isolates were grouped into 35 sequence types (STs) that belonged to 25 clonal complexes (CCs) and one singleton (ST619) by multi-locus sequence typing. The most prevalent ST was ST9 (26.9%), followed by ST8 (17.9%), ST87 (15.3%), ST155 (9.4%), and ST121 (7.6%). Thirty-seven isolates harboured the llsX gene (representing LIPI-3), and they belonged to ST1/CC1, ST3/CC3, ST288/CC288, ST323/CC288, ST330/CC288, ST515/CC1, and ST619, among which ST323/CC288, ST330/CC288, and ST515/CC1 were newly reported to carry LIPI-3. Seventy-five isolates carried ptsA, and they belonged to ST87/CC87, ST88/CC88, and ST619, indicating that consumers may be exposed to hypervirulent L. monocytogenes. Antibiotics susceptibility tests revealed that over 90% of the isolates were susceptible to 11 antibiotics; however, 40.0% of the isolates exhibited resistance against ampicillin and 11.8% against tetracycline; further, 45.0% and 4.6% were intermediate resistant and resistant to ciprofloxacin, respectively. The rise of antibiotic resistance in L. monocytogenes suggests that stricter regulations should be formulated to restrict the use of antibiotic agents in human listeriosis treatment and livestock breeding.